(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
India has growth prospect for retail industry with a hugenumber of consumers and other favorable factors. But India’s retail marketremains largely off-limits to large international retailers like Wal-Mart,Tesco and Carrefour. Opposition to liberalizing FDI in this sector raisesconcerns about employment losses, unfair competition resulting in large-scaleexit of incumbent domestic retailers and infant industry arguments to protectthe organized domestic retail sector that is at a nascent stage. In 2012 theIndian Government approved proposal of100 percent FDI in retailing in India subject to certain conditions.Though this proposal is being hailed byglobal retail giants, which until now have been involved in only wholesale cash and carry distribution in India and have been longing for entry into the Indian retail market foryears. The proposal has receivedvehement opposition from a spectrum of political parties in India, many of themurging for a reversal of the proposal. As a result, the Indian government has stalled the implementation of this proposalwhich has temporarily washed off the wishes of the global retail players awaiting a bite of the Indian retail market. This paper attempts to studythe present status of FDI in retailing sector in India and the impacts of FDIon various concerned segments.